Being brown : Sonia Sotomayor and the Latino question - Lima, Lázaro (Oakland, California : University of California Press, 2020)
"Sonia Sotomayor is the highest ranking Latino/a in the United States. Her story of accomplishment and rise to the pinnacle of American public life seemed to herald a profound cultural and historical shift. Latinos are America's largest minority and also its most disenfranchised. For many, Sotomayor's ascent represented the elusive fulfillment of an American dream. A chronological narrative of her extraordinary life, Being Brown juxtaposes Sotomayor's phenomenal successes with the twists and turns of minority inclusion in American democracy. Lázaro Lima also shows how Sotomayor's own self-making as a Puerto Rican model of possibility allows us to understand not only the appeal but also the limits of representation. Culling through Sotomayor's own writings, her Supreme Court dissents, and speeches, Lima questions what it means to have a powerful Latina in the Supreme Court. What does her ascent say about social mobility and inclusion? While Sotomayor's story inspires hope, it also reveals much about the general lack of equality of Latinos and other disenfranchised communities"--Provided by publisher.
Introduction : on being brown in the democratic commons -- Sonia Sotomayor and "the Latino question" -- Sonia Sotomayor's elusive embrace -- Sonia Sotomayor, the mediapheme -- Sonia Sotomayor and other states of debt -- Coda : thinking otherwsie.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher.
In English.
JSTOR
Keywords: Sotomayor, Sonia, -- 1954-; Sotomayor, Sonia, -- 1954-; Judges -- United States -- Biography; Hispanic American judges -- Biography; Juges -- États-Unis -- Biographies; Juges américains d'origine latino-américaine -- Biographies; HISTORY / Social History; Hispanic American judges; Judges; United States; accomplishment; american public life; civil rights policies; democratic practice; first latina supreme court justice; greater acceptance; historical moment; icon; inclusion of latinos; insurmountable odds; meaningful political enfranchisement; minority majority; possibly model; profound demographic transformation; resurgent racism; safeguards; success; symbolic inclusion; uncritical embrace; Biographies